37.3k views
2 votes
Help me Please I need it !

Help me Please I need it !-example-1

2 Answers

5 votes

Answer:

f(x) = 38

Explanation:

To find f(x), we must evaluate the expression: x^2 - 4x + 6 when x = -4

Let's break this down:

The first part of this equation is x^2. Plug in -4 for x and solve: -4^2 = 16

Next is -4x. Once again, substitute x with -4, and you have: -4(-4) = 16

And finally, the last part of the expression is just 6, which is a constant, so no solving is necessary.

Now take all the parts of your expression and piece them back together:

16 + 16 + 6 should be the final expression you get.

Solve that expression: 16 + 16 + 6 = 38

Plug the answer back into the equation, and you'll get f(x) = 38.

Hope this helps!

User Gerry P
by
5.6k points
0 votes

Answer:

38

Explanation:

Given that,

x = -4

f(x)=x² - 4x +6

so,

f(-4)= (-4)² - 4 . (-4) +6

=16 +16 +6

= 38

User Dominik Reinert
by
5.6k points